Gender of transformational school principals and teachers’ innovative behavior - Aziah Ismail; Nor Shafrin Ahmad; Rahimi Che Aman (International Journal of Evaluation and Research in Education (IJERE), 2021)
The purpose of this paper is to examine the different levels of transformational leadership between male and female principals and their relationships with teachers' Innovative Work Behavior (IWB) in Malaysian secondary schools. In total, 477 teachers from various secondary schools were randomly selected as respondents (218 are working under female principals, while 259 of them are under male principals). This study revealed that the respondents agree that male principals practice transformational leadership higher than female principals. However, the female principals were highly influential on the teachers’ IWB compared to their male counterparts. This study provides a glimpse of the teachers' innovative behavior improvement resulted from transformational leadership by male and female school principals.